Introduction to the special issue on joint modelling techniques. (February 2014) - Rizopoulos, Dimitris; Lesaffre, Emmanuel
Joint modelling techniques have seen great advances in the recent years, with several types of joint models having been developed in literature that can handle a wide range of applications. This special issue of Statistical Methods in Medical Research presents some recent developments from this field. This introductory article contains some background material and highlights the contents of the contributions.